The Role and Role of Artificial Intelligence in Science and Economy - Yusupova Feruza Erkinovna (Genius Journals, 2023)
In this article, you will learn about "artificial intelligence" which has become a hot topic these days. In the article what is artificial intelligence?, History of artificial intelligence, stages of development?, Is artificial intelligence a threat to humanity? We will try to find answers to such questions.
Keywords: Artificial intelligence; Intellectual property; ICT